A matter of credibility: Conventional and nuclear security commitments of the United States in Europe - Marco Overhaus (Stiftung Wissenschaft und Politik (SWP), 2019)
US President Donald Trump has cast doubt on his country's security commitments within NATO by his "America First" programme and his verbal attacks on the Alliance. This affects both conventional reassurance, i.e. pledges to allies backed by non-nuclear military means, and nuclear reassurance. Beyond the "Trump factor", the costs and risks associated with these security commitments have increased from Washington's perspective. The reasons are the expansion of the Alliance territory through its eastern enlargement, the modernisation of the Russian military, and the end of the US's undisputed military supremacy. Nevertheless, during the Trump administration, the US has not reduced but increased its financial and military contributions to the reassurance of its allies. Uncertainties about the US's role in NATO have led to deepening rifts in Europe. On one side are the European allies that are striving for a higher degree of "strategic autonomy" from Washington, and on the other those who want to lean even more on the US as a protecting power. From the perspective of many eastern NATO states, American security promises are more credible than potential European alternatives, even during the Trump administration. The credibility of American security commitments is a multifaceted issue that cannot be reduced to statements by the US President. European NATO states consider and weight the underlying factors differently. Political deci-sion-makers, not least in Germany, must be alert to these differences for the sake of political cohesion in the EU and NATO.
Keywords: 320